The Portrayal of Geisha as Japanese Culture in â€œMemoirs of Geishaâ€ Movie Directed by Rob Marshall - Muh Ferdivahlevi Aca; Ansor Putra (Program Studi Sastra Inggris Fakultas Ilmu Budaya Universitas Halu Oleo, 2019)
This study focuses on the analysis of the Portrayal of Geisha in â€œMemoirs of Geishaâ€ Movie Directed by Rob Marshall. It aimed to study how geisha is portrayed in this Movie as Japanese Culture. In this study, the writer uses the descriptive method, by applying the Multicultural Feminism respective in analyzing this Memoirs of Geisha Movie. Geisha was born from a movement of women who tried to live independently in the Meiji period. Geisha is a profession among Japanese women at that time as one of the best jobs for a woman at that time. This study illustrates how Geisha plays an important role in improving the quality of life for women in Japan. Even so, Geisha has a very bad controversy because of the cultural differences that occur between Japan and western culture. Japanese tradition that seems taboo to be done by common people, makes Geisha as one of the controversial cultures. Despite Geisha have a bad value in the western view, Geisha herself has a firm ideology of culture and themselves.